Identifikasi Potensi Mineral Nikel Laterit Menggunakan Data Geomagnetik EMM (Enchanted Magnetic Model) 2017 di Kecamatan Poli Polia - Keisyah Putri Islami; Arif Budiman (Universitas Andalas, 2026)
A study has been conducted utilizing secondary geomagnetic data from the Enhanced Magnetic Model (EMM) 2017. This study aims to identify the potential presence and lateral distribution of laterite nickel minerals in Poli Polia District. The data processing stages include International Geomagnetic Reference Field (IGRF) correction, Reduce to Pole (RTP) transformation, and separation of regional and residual anomalies. Furthermore, analysis and interpretation are carried out by comparing the residual anomaly map to the regional geological map. The results of the RTP transformation obtained residual magnetic anomaly values ​​ranging from -0.8 nT to 0.7 nT with high anomaly values ​​ranging from 0.5 nT to 0.7 nT and low values ​​ranging from -0.8 nT to -0.6 nT. In the southwest of the study area there is a low magnetic anomaly zone surrounded by a low magnetic anomaly zone, while in the north it is the opposite. The results of data interpretation indicate that the high anomaly zone in the southwest is related to the presence of the Ultramafic Complex (Ku) composed of peridotite and serpentine rocks, while the low anomaly zone is interpreted as a prospective area containing laterite nickel minerals. Meanwhile, in the northern part, the low anomaly zone correlates with the Mekongga Complex (Pzm), which is composed of metamorphic and sedimentary rocks. The presence of a high anomaly zone in this area indicates the presence of geological features such as faults or joints that play a significant role in enhancing the local magnetic response.